Transient Hypothyroidism: Dual Effect on Adult-Type Leydig Cell and Sertoli Cell Development - Rijntjes, Eddy; Gomes, Marcos L. M.; Zupanič, Nina; Swarts, Hans J. M.; Keijer, Jaap; Teerds, Katja J. (Frontiers in Physiology, 2017)
Transient neonatal 6-propyl-2-thiouracil (PTU) induced hypothyroidism affects Leydig and Sertoli cell numbers in the developing testis, resulting in increased adult testis size. The hypothyroid condition was thought to be responsible, an assumption questioned by studies showing that uninterrupted fetal/postnatal hypothyroidism did not affect adult testis size. Here, we investigated effects of transient hypothyroidism on Leydig and Sertoli cell development, employing a perinatal iodide-deficient diet in combination with sodium perchlorate. This hypothyroidism inducing diet was continued until days 1, 7, 14 or 28 postpartum (pp) respectively, when the rats were switched to a euthyroid diet and followed up to adulthood. Continuous euthyroid and hypothyroid, and neonatal PTU-treated rats switched to the euthyroid diet at 28 days pp, were included for comparison. No effects on formation of the adult-type Leydig cell population or on Sertoli cell proliferation and differentiation were observed when the diet switched at/or before day 14 pp. However, when the diet was discontinued at day 28 pp, Leydig cell development was delayed similarly to what was observed in chronic hypothyroid rats. Surprisingly, Sertoli cell proliferation was 6- to 8-fold increased two days after the diet switch and remained elevated the next days. In adulthood, Sertoli cell number per seminiferous tubule cross-section and consequently testis weight was increased in this group. These observations implicate that increased adult testis size in transiently hypothyroid rats is not caused by the hypothyroid condition per se, but originates from augmented Sertoli cell proliferation as a consequence of rapid normalization of thyroid hormone concentrations.